2013
DOI: 10.1037/a0032359
|View full text |Cite
|
Sign up to set email alerts
|

On psychological growth and vulnerability: Basic psychological need satisfaction and need frustration as a unifying principle.

Abstract: Humans have a potential for growth, integration, and well-being, while also being vulnerable to defensiveness, aggression, and ill-being. Self-Determination Theory (Ryan & Deci, 2000b) argues that satisfaction of the basic psychological needs for autonomy, competence, and relatedness both fosters immediate well being and strengthens inner resources contributing to subsequent resilience, whereas need frustration evokes ill-being and increased vulnerabilities for defensiveness and psychopathology. We briefly rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

153
1,550
8
76

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,515 publications
(1,787 citation statements)
references
References 116 publications
153
1,550
8
76
Order By: Relevance
“…For example, we might expect that controlling speakers would be perceived to be more pressuring, and as a result participants would feel pressured. We furthermore tested whether prosody could also shape well-being, given autonomy-supported individuals experience more happiness and self-esteem, and lower anxiety, than those who are being controlled (e.g., O'Rourke et al, 2012;Reis et al, & Ryan, 2000;Vansteenkiste & Ryan, 2013). We expected that listening to autonomy-supportive prosody would improve well-being.…”
Section: Studymentioning
confidence: 99%
“…For example, we might expect that controlling speakers would be perceived to be more pressuring, and as a result participants would feel pressured. We furthermore tested whether prosody could also shape well-being, given autonomy-supported individuals experience more happiness and self-esteem, and lower anxiety, than those who are being controlled (e.g., O'Rourke et al, 2012;Reis et al, & Ryan, 2000;Vansteenkiste & Ryan, 2013). We expected that listening to autonomy-supportive prosody would improve well-being.…”
Section: Studymentioning
confidence: 99%
“…In the context of pain, the challenge is to keep engaging in activities for autonomous instead of controlled reasons, key of which may be the continued satisfaction of these basic needs. In contrast, need thwarting may give rise to compensatory behaviours such as diminished self-control (manifested through for instance alcohol or medication abuse) and rigid behavioural patterns (Vansteenkiste and Ryan, 2013). In the latter case, individuals may compulsively stick to certain behavioural patterns because they provide a sense of predictability and security (Vansteenkiste and Ryan, 2013).…”
Section: Self-determination Theory: the Role Of Psychological Need Samentioning
confidence: 99%
“…In contrast, need thwarting may give rise to compensatory behaviours such as diminished self-control (manifested through for instance alcohol or medication abuse) and rigid behavioural patterns (Vansteenkiste and Ryan, 2013). In the latter case, individuals may compulsively stick to certain behavioural patterns because they provide a sense of predictability and security (Vansteenkiste and Ryan, 2013). In the context of pain, individuals may for instance persistently try to avoid activities which they think will augment their pain, depriving them from activities which may potentially satisfy their basic psychological needs.…”
Section: Self-determination Theory: the Role Of Psychological Need Samentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, autonomy frustration is characterized by feelings of pressure and inner conflict, for instance, when prisoners feel forced to take part in nonvalued activities. We focus specifically on the need for autonomy (rather than the needs for competence and relatedness) as perceived afforded choice, another key variable in the current study, is expected to relate most strongly to autonomy (see Reeve, Nix, & Hamm, 2003; but see Patall, Cooper, & Robinson, 2008 for a link with competence).An extensive body of empirical work underscores the benefits associated with autonomy satisfaction and the mental health costs associated with autonomy frustration (for an overview see Vansteenkiste & Ryan, 2013). To illustrate, in an earlier study, Vansteenkiste, Lens, Soenens, and Luyckx (2006) reported that in a sample of Chinese immigrants autonomy satisfaction related positively to positive affect, life satisfaction and vitality, while being negatively related to depressive symptoms.…”
mentioning
confidence: 99%